Rates of risk‐reducing surgery in Israeli BRCA1 and BRCA2 mutation carriers. (9th April 2013) - Laitman, Y; Vaisman, Y; Feldman, D; Helpman, L; Gitly, M; Paluch Shimon, S; Berger, R; Cohen, L; Narod, SA; Friedman, E
<x xml:space="preserve">Abstract</x> The frequency of BRCA1 and BRCA2 mutations is higher in Israel than in almost all other countries. One strategy to reduce the burden of hereditary breast and ovarian cancers is to offer genetic testing followed by risk‐reducing surgery (mastectomy and salpingo‐oophorectomy) for mutation carriers. The extent to which Israeli women who carry mutations undergo these surgeries is not well characterized. Israeli women who are BRCA1 or BRCA2 mutation carriers and followed at a single high‐risk clinic were asked to complete a questionnaire detailing their clinical histories at the time of genetic results disclosure and a follow‐up questionnaire was completed 18 or more months thereafter. A total of 205 mutation carriers completed the questionnaires. Of 170 women with no cancer history, 84 (49%) had a risk‐reducing bilateral salpingo‐oophorectomy and 22 (13%) had a risk‐reducing mastectomy. Five of 35 (14.3%) women with breast cancer opted for contralateral mastectomy. Approximately one half of Israeli women with a BRCA1 or BRCA2 mutation opt for risk‐reducing oophorectomy, but the rate of risk‐reducing mastectomy is only 13%.